2023
DOI: 10.1002/ece3.9971
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant availability trades off with warning signals and toxin sequestration in the large milkweed bug (Oncopeltus fasciatus)

Abstract: In some aposematic species the conspicuousness of an individual's warning signal and the concentration of its chemical defense are positively correlated. Several mechanisms have been proposed to explain this phenomenon, including resource allocation trade-offs where the same limiting resource is needed to produce both the warning signal and chemical defense. Here, the large milkweed bug (Oncopeltus fasciatus: Heteroptera, Lygaeinae) was used to test whether allocation of antioxidants, that can impart color, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Such research could also shed more light on whether there are costs associated with the biosynthesis of different cardenolides (e.g., those with extra glycosylation, or further modifications to the sugar moiety), and the cost-benefit of producing specific cardenolides in relation to differences in insect diversity, herbivore specialization, and the constraints on those herbivores. Although Agrawal et al (2022) found no significant effects of the most potent inhibitors on O. fasciatus growth and performance, we have recently shown that sequestration can be costly in terms of oxidative state (Blount et al, 2023;Heyworth et al, 2023) which is visible in the wing colors that milkweed herbivores use as anti-predator defenses. More tests on the costs of sequestration will also be important for understanding the evolutionary and ecological interactions between the plant and the herbivore.…”
Section: Synthesismentioning
confidence: 80%
“…Such research could also shed more light on whether there are costs associated with the biosynthesis of different cardenolides (e.g., those with extra glycosylation, or further modifications to the sugar moiety), and the cost-benefit of producing specific cardenolides in relation to differences in insect diversity, herbivore specialization, and the constraints on those herbivores. Although Agrawal et al (2022) found no significant effects of the most potent inhibitors on O. fasciatus growth and performance, we have recently shown that sequestration can be costly in terms of oxidative state (Blount et al, 2023;Heyworth et al, 2023) which is visible in the wing colors that milkweed herbivores use as anti-predator defenses. More tests on the costs of sequestration will also be important for understanding the evolutionary and ecological interactions between the plant and the herbivore.…”
Section: Synthesismentioning
confidence: 80%
“…The variability in the bug’s sequestration behaviour in our study cannot alone be accounted for by the cardenolide content of the host plant because the bugs in our study were provided with an ad libitum supply of seeds of A. curassavica . This within population variation may reflect genetic differences in the individuals’ capacity to sequester [ 54 ], differences in individual physiological state [ 55 , 56 ] or the absence of predation pressure and the relaxed selection in the laboratory [ 53 ]. The higher variance in the concentration of cardenolides in the defensive fluid could also be owing to the fact that we were only able to collect a fraction of the DLS content during manual stress.…”
Section: Discussionmentioning
confidence: 99%
“…The variance could also reflect sex differences in sequestration, but we found no differences between male and female cardenolide concentrations in the DLS fluid (see the electronic supplementary material, S6 and also Moore and Scudder [ 17 ]). We did not control for insects’ reproductive stage, or age, which might contribute to variation [ 56 ]. Testing whether predators are able to detect the variation present in the chemical defence will be important for understanding if such variation is subject to differential selection and therefore how intraspecific variation in chemical defence concentration can be maintained [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a study showed a physiological association in D. plexippus between oxidative stress (measured by oxidative lipid damage), cardenolide sequestration, and warning colouration ( Blount et al, 2023 ). Interestingly, in Oncopeltus fasciatus , the amount of sequestered cardenolides depleted the redox state (measured by the total glutathione level) and antioxidant availability was traded off with brightness and chroma signals ( Heyworth et al, 2023 ). Although very few studies have supported the physiological cost of toxin sequestration in aposematic insects, there is still a lack of evidence that toxin sequestration, warning signals (pigments), and oxidative stress are interlinked.…”
Section: Physiological Costsmentioning
confidence: 99%